Entre a morte trágica e a morte histórica: considerações sobre o imaginário fúnebre na Atenas do século V A.C. - Gomes, Caio Cesar Machado (2019)
This work aims to investigate the process of social construction of a funerary imaginary in Athens of the fifth-century BC, taking as a starting point the senses and meanings attributed to the death in works by the tragedy writer Euripides (Alcestis, Herakleidae, and Hecuba) and the historian Thucydides (History of the Peloponnesian War). The central idea is to think of possible continuities and ruptures regarding the ideals and death policies carried out by the Athenians during the course of the fratricidal war between the Greeks, with special emphasis on the first years of the conflict. In addition to the phenomenon of death and post-mortem’s reflections, the proposal is also to analyze how funerary habits and their intrinsic relation with the war traditions are present and at what extent they are representative in the tragic and historiographic productions.